Characterization of myeloid neoplasms following allogeneic hematopoietic cell transplantation. Issue 2 (16th November 2021) - Kuno, Masatomo; Yamasaki, Satoshi; Fujii, Nobuharu; Ishida, Yasushi; Fukuda, Takahiro; Kataoka, Keisuke; Uchida, Naoyuki; Katayama, Yuta; Sato, Maho; Onai, Daishi; Miyamoto, Toshihiro; Ota, Shuichi; et al.
Abstract: We compared characteristics of myeloid neoplasms (MNs) following allogeneic hematopoietic cell transplantation (HCT) versus autologous HCT using a Japanese HCT registry database. Among 43 788 patients who underwent allogeneic ( n  = 18 874) or autologous HCT ( n  = 24 914) for non‐myeloid malignancies or non‐malignant diseases, 352 developed MNs. The cumulative incidence of MNs was lower after allogeneic HCT than after autologous HCT (0.3% vs. 1.8% at 10 years, respectively, p  < .001). Compared with autologous HCT, MNs following allogeneic HCT developed in younger patients (median, 42 vs. 57 years old, respectively) and sooner after HCT (median, 16 vs. 33 months, respectively). Approximately half of MNs following allogeneic HCT were donor‐derived and occurred later than recipient‐derived MNs (median, 26 vs. 6 months, respectively, p  = .003). In multivariate analysis, reduced‐intensity conditioning and cord blood transplantation were associated with MN development after allogeneic HCT. Overall survival was similar in patients who developed MNs following allogeneic versus autologous HCT (18% vs. 22% at 5 years, respectively, p  = .48). Patient age ≥ 55 years, the presence of previous HCT, AML subtype, and chromosome 5 or 7 abnormalities were adverse factors for overall survival after MN diagnosis. Further research is warranted to elucidate the mechanisms of MN development following allogeneic HCT.